The Role of Green Intellectual Capital on Competitive Advantage: Evidence from Balinese Financial Institution - Anak Agung Putu Gede Bagus Arie Susandya; Putu Diah Kumalasari; Ida Ayu Ratih Manuari (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
The purpose of this study is to analyze the role of green intellectual capital on competitive advantage of Lembaga Perkreditan Desa (Balinese Financial Institution). The study tested by using data collected from a sample of 120 respondents that were randomly picked from 35 Lembaga Perkreditan Desa in Denpasar. Findings suggested that green human capital, green relational capital, and green structural capital affect competitive advantage at 17.6%. This study has found that green human capital, green relational capital, and green structural capital have an effect on competitive advantage. Furthermore, green human capital and green structural capital had positive effect on competitive advantage. Meanwhile, green relational capital had no effect on competitive advantage. The ecofriendly concept remains a critical factor to gain company’s competitive advantage. This study provides insight into green innovation research field.